Athletes' careers across cultures (Routledge, 2013)
Tatiana V. Ryba and Natalia B. Stambulova, Turn to a Culturally Informed Career Research and Assistance in Sport Psychology. Tim Chambers, Sandy Gordon, and Tony Morris, Athletes` Careers in Australia: From Retirement to Education and Beyond. Paul Wylleman, Anke Reints, and Paul De Knop, Athletes` Careers in Belgium: A Holistic Perspective to Understand and Alleviate Challenges Occurring throughout the (Post-)Athletic Career. Maria Regina Ferreira Brandao and Lenamar Fiorese Vieira, Athletes` Careers in Brazil: Research and Application in the Land of Ginga. Robert J. Schinke, Jessica Cummings, and Justin Bonhomme, Athletes` Careers in Canada: Four Decades of Research and Practice. Zhijian Huang, Menglin Chen, and Na Qiao, Athletes` Careers in China: Advances in Athletic Retirement Research and Assistance. Kristoffer Henriksen and Mette Christensen, Athletes` Careers in Denmark: Nurturing Athletic Talents. Nadine Debois and Véronique Leseur, Athletes` Careers in France: In Pursuit of Excellence in Sport and Life. Dorothee Alfermann and Franziska Preis, Athletes` Careers in Germany: Research and Assistance Programs. Stiliani "Ani" Chroni, Eleni Diakaki, and Athanasios Papaioannou Athletes` Careers in Greece: Impulses for Culturally Infused Future. Norishige Toyoda, Athletes` Careers in Japan: Before and After Termination in Sports. Cristina Fink, Athletes` Careers in Mexico: Learning How to Handle Transitions. Christina Ryan and Holly Thorpe, Athletes` Careers in New Zealand (Aotearoa): The Impact of the Graham Report and the Carding System. Natalia Stambulova and Elena Hvatskaya, Athletes` Careers in Russia: From 1980 Moscow to 2014 Sochi Olympics. Sasa Cecic Erpic, Athletes` Careers in Slovenia: Remarkable Sporting Achievements of a Small Country. Miquel Torregrosa and M Dolores González Athletes` Careers in Spain: Professionalization and Developmental Consequences. Natalia Stambulova and Urban Johnson Athletes` Careers in Sweden: Facilitating Socialization into Sports and Re-Socialization upon Retirement. Sunghee Park, David Lavallee, and David Tod, Athletes` Careers in the United Kingdom and the Republic of Ireland: Differences in the Evolution of Research and Support Programs between the Two Neighbor Nations. Albert Petitpas, Judy Van Raalte, & Britton Brewer, Athletes` Careers in the United States: Developmental Programming for Athletes in Transition. Natalia B. Stambulova and Tatiana V. Ryba, Setting the Bar: Towards Cultural Praxis of Athletes` Careers.